As you like it [Ako sa Vám páči anglicky] - Shakespeare, William, 1564-1616; Macaw Books (Leicester : Sweet Cherry Publishing : [distributor] Sweet Cherry Publishing, 2020)
"All the world´s a stage..." One of the most quoted lines of Shakespeare was first heard in this play. "As you like it" is set in the enchanted Forest of Arden, where Rosalind, the daughter of an exil duke, and Orlando, the son of one of her father´s courters, become entangled in a game of love and mistaken identity.
A short narrative version of the play has been suitably adapted to help to introduce the play to young readers.
Keywords: Children's stories; čítam si sám (7+); cudzojazyčná literatúra